Konsep Epistemologi dalam Islam: Kajian Tentang Sumber dan Cara Memperoleh Pengetahuan - Nazwa Hariyanto; Febry Wulandari; Nadia Salwa (Journal Islamic Studies of Muhammadiyah, 2026)
The rapid development of science and technology in the digital era has generated various epistemological challenges, particularly concerning the validity of information, the authority of knowledge, and the ways in which knowledge is acquired. These challenges highlight the need to strengthen the study of Islamic epistemology as a paradigm that integrates rational, empirical, and spiritual dimensions in the construction of knowledge. This study aims to examine the concept of Islamic epistemology by focusing on the sources of knowledge, the methods of acquiring knowledge, and their relevance to the development of contemporary science. This research employs a qualitative approach using a library research method. The data were collected from the Qur'an, Hadith, classical and contemporary works of Muslim scholars, as well as relevant academic literature. The data were analyzed through content analysis using a philosophical approach involving data classification, interpretation, and conceptual synthesis. The findings reveal that Islamic epistemology is founded upon the integration of revelation (wahy), reason ('aql), sensory perception, and intuition as complementary sources of knowledge. Knowledge is acquired through observation, rational inquiry, learning, and spiritual purification, all of which are grounded in the principle of tawhid. Furthermore, the study demonstrates that Islamic epistemology remains highly relevant in addressing contemporary scientific and technological challenges by providing a conceptual framework that integrates scientific validity with ethical and spiritual responsibility.